Peran AUKUS dalam Strategi Diversifikasi Pasar Ekspor Australia Pasca Sanksi Dagang Tiongkok Tahun 2021 - Dwi Azzahra Wulandari; Putri Novelita Simbolon; Efrina Dwi Antesa (Department of International Relations, Brawijaya University, 2025)
This study examines the role of AUKUS in Australia’s export market diversification strategy following China’s trade sanctions in 2021. Diplomatic tensions between the two nations led to restrictions on key Australian exports such as coal, barley, and wine, significantly affecting the national economy. Using a qualitative descriptive approach, this research analyzes Australia’s policies to expand its export markets toward alternative partners such as India, Japan, and South Korea, while assessing AUKUS’s contribution to economic resilience through defense cooperation, technological collaboration, and strategic investments. The findings reveal that AUKUS serves not only as a defense alliance but also as an instrument of economic diplomacy that strengthens Australia’s ties with Western allies, fosters new investment opportunities, and supports its foreign policy autonomy in the Indo-Pacific region. Therefore, AUKUS plays a crucial role in maintaining Australia’s economic and political stability amid growing global geopolitical competition.